Paradigma Kearsipan dalam Keterbukaan Informasi Publik di PT Semen Padang - Irfan, Muhammad; Desriyeni, Desriyeni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2014)
This article discusses the archival paradigm in the disclosure of public information on PT. Semen Padang. The writing is aimed at obtaining a description of: (1) archival paradigm in public disclosure in PT. Semen Padang; (2) constraints encountered in archival paradigm in PT. Semen Padang; (3) ways in which to overcome these obstacles. By analyzing the data, it was concluded that: first, at PT. Semen Padang on archival paradigm is good because the existing information and information received can already be identified quickly by work units and employees to see archival websites, newsletters, recor center archives and other information systems used by PT. Semen Padang; second, obstacles encountered in the archives at. Semen Padang presence of several units that have not been able to understand about the archives or the management of PT. Semen Padang; Third, as for the method to overcome these obstacles is to hold weekly or monthly socialization of archives and archival procedures and conduct future Jop On Training on electronic filing. This makes the user community paradigm of archival records have not been entirely good. Keywords: paragdima; archives; public information